A three-dimensional color space from the 13th century. - Smithson, H; Dinkova-Bruun, G; Gasper, G; Huxtable, M; McLeish, T; Panti, C (2012)
We present a new commentary on Robert Grosseteste's De colore, a short treatise that dates from the early 13th century, in which Grosseteste constructs a linguistic combinatorial account of color. In contrast to other commentaries (e.g., Kuehni and Schwarz, Color Ordered: A Survey of Color Order Systems from Antiquity to the Present, 2007, p. 36), we argue that the color space described by Grosseteste is explicitly three-dimensional. We seek the appropriate translation of Grosseteste's key terms, making reference both to Grosseteste's other works and the broader intellectual context of the 13th century, and to modern color spaces.